Effect of Nutritive and Non-Nutritive Sweeteners on the Lipid Profile, Castelli Index I and II, and Atherogenic Index of Plasma Using Experimental Rat Models - Ruth T. Owu; Efua E. Annan; Joana Ainuson-Quampah; Matilda Asante; Charles Addoquaye Brown; George A. Asare (Journal of Nutrition and Metabolism)
Previous research on sweeteners’ effect on health has focused on indices of cardiometabolic risk factors without considering lipid ratios such as the Atherogenic Index of Plasma (AIP) and Castelli Risk Index I and II (CRI-I and CRI-II). The study sought to evaluate the effect of natural sweeteners on lipid profiles and lipid ratios. Seventy-eight female Sprague Dawley rats (6 rats per group) were administered with different doses of sweeteners (3 groups per sweetener): white sugar (0.035 g/mL, 0.07 g/mL, and 0.1 g/mL), brown sugar (0.036 g/mL, 0.072 g/mL, and 0.11 g/mL), honey (0.047 g/mL, 0.094 g/mL, and 0.14 g/mL) and stevia (0.004 g/mL, 0.014 g/mL, and 0.021 g/mL) for 17 weeks. The highest weight gain was observed with high-dose stevia administration (72.7 g ± 10.5). The group administered with high dose of white sugar had the highest CRI-I (1.79 ± 0.11) and CRI-II (0.49 ± 0.09). CRI-I and CRI-II had a dose-dependent increase with white sugar. The AIP was highest in the high-dose stevia group (0.21 ± 0.07) with dose-dependent increases within the stevia group. High intakes of white sugar and stevia tend to promote the development or progression of atherosclerosis.